ANALISIS TINGKAT MENABUNG MAHASISWA DI UNIVERSITAS ISLAM MALANG DAN UNIVERSITAS MUHAMMADIYAH MALANG - Nuril Laili Wulandari; Abdul Wahid Mahsuni; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this study is to determine how much influence the Level ofReligiosity, and Disposable Income to the interest of saving. The population arebachelor student of Accounting in Faculty of Economics and Business inacademic year 2014, University of Islam Malang and University ofMuhammadiyah Malang. Type of this research by using field research inquantitative approach. This research uses isendental sampling technique, whilefor data collection technique is done by using questionnaire method. Samplestaken using Slovin formula.The result of the calculation sample taken in this study 10% or as many as100 respondents. The data analysis used descriptive statistical analysis, validitytest, reliability, normality, classical assumption, multiple linear regression, andhypothesis testing by using SPSS program. Based on the analysis result show thatthe level of Religiosity has a significant influence on the proclivity of saving bystudent in Islamic Banking either partially or simultaneously while DisposableIncome has an influence on the variable interest in saving simultaneously but ithas no partial influence.Keywords: The Level of Religiosity, Disposable Income, and Interest Saving